DYNAMICS OF INTERNATIONAL TOURISM AT GLOBAL LEVEL - Oana Ruxandra BODE (Studia Universitatis Babeş-Bolyai Negotia, 2018)
The core idea of the present paper is to analyse the evolution of international tourism during 2000-2015, simultaneously highlighting the factors that contribute to this dynamic. Thus, the aim of this paper is two-fold. The first is to analyse the evolution of international tourism at global level and at regional level. The second is to screen the dynamics of international tourism in the top tourism destinations countries. The main reason of focusing the research in this area is given by the important part played by tourism, a diverse and complex industry, in the global economy.